Playing in Tongues: The Hammond Organ and Black Pentecostal Instrumentality - Braxton D. Shelley (Music & Science)
This article attends to the social life of the Hammond organ in the Black Pentecostal imaginary, a theological, cultural, and musical phenomenon that calls attention to the social fact of instrumental timbre. Grounded in an analysis of Hammond organ solos by Elbernita “Twinkie” Clark, one of the most renowned organists in the Black gospel tradition, I argue that this gospel practice uses arresting timbral transformations to articulate the escalatory cultural logic that has elsewhere been termed “tuning up.” This “tuning up” achieves on the organ what is enacted by the transition from speech to song in the sermon and through a host of harmonic, metrical, and textural changes in the gospel song. Woven into a suite of idiomatic keyboard techniques, Clark’s idiom, and the broader performance practice she represents, deploys the 88 8888 888 drawbar registration that is explicitly discouraged in Hammond organ user manuals as a timbral telos—a defined ecstatic threshold that orients the sonic trajectory of an organ solo. Timbre is often seen as a multidimensional, indiscrete musical parameter. Yet this gospel organ technique shows how each nine-drawbar set provides the coordinates for its own distinct timbral space, enabling musicians to map these spaces onto corresponding paths of musical, spiritual, and physical intensification. Each of the journeys stages a moment of startling conversion, where one element of the instrument’s voice is overcome by another. Clark’s playing is an invaluable window into the confessional dimensions of gospel’s timbral practice. Building on scholarship in Black studies, music studies, critical organology, and religious studies, I argue that these points of inflection—which I refer to as flips—reveal a Black Pentecostal instrumentality, and the key to the Hammond organ’s appeal.